Durability based suitability of bagasse-cement composite for roofing sheets (2012)
Accelerated and natural weathering of bagasse reinforced cement composite filled with rice ash pozollan used as roofing sheets were studied. In this paper, the durability of natural fibers such as sugarcane bagasse used as roofing sheets has been reported by conducting an experimental investigation. This investigation includes determination of mechanical strength properties such as compressive, tensile, modulus of rupture and flexural properties of the roof once every 3 months for a period of 8 years under alternate wetting and drying conditions and was exposed to ultraviolet light for the same period. The 8 years study showed no significant difference in the strength and sorption properties for the treated bagasse at 2% CaCl2 and the 20% replacement of cement with rice husk ash. This confirms that treated bagasse cement composite is suitable for both external and internal construction purposes.